2008
DOI: 10.3102/0002831208318259
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Personal Predictors of Teacher Commitment: The Mediating Role of Teacher Efficacy and Identification With School

Abstract: This study tested a predictive and mediation model of teacher commitment. Teacher efficacy and sense of identification with school were hypothesized to mediate the relations of an individual antecedent (teaching experience) and two organizational antecedents (perceived organizational politics and reflective dialogue) to teacher commitment. Multigroup structural equation modeling was used to test and validate the mediation model across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
2
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 53 publications
(75 reference statements)
11
133
2
17
Order By: Relevance
“…The roles of teacher are pertinent in ensuring the success of students in furthering their tertiary level education from their common primary and secondary school education. With the current Malaysian education system that is constantly introducing changes and reviews in education policies (Ministry of Education, 2011), school teachers are the vital people who will execute educational plans (Chan, 2008;Park, Henkin, & Egley, 2005). Hence, teacher efficacy is pertinent as it affects greatly the students' learning outcomes (Caprara, Barbaranelli, Steca, & Malone, 2006;Dellinger et al, 2008;Robinson, Lloyd, & Rowe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of teacher are pertinent in ensuring the success of students in furthering their tertiary level education from their common primary and secondary school education. With the current Malaysian education system that is constantly introducing changes and reviews in education policies (Ministry of Education, 2011), school teachers are the vital people who will execute educational plans (Chan, 2008;Park, Henkin, & Egley, 2005). Hence, teacher efficacy is pertinent as it affects greatly the students' learning outcomes (Caprara, Barbaranelli, Steca, & Malone, 2006;Dellinger et al, 2008;Robinson, Lloyd, & Rowe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among these are protective factors that include attributes such as altruism (Brunetti, 2006;Chong & Low, 2009), strong intrinsic motivation (Flores, 2006;Kitching, Morgan, & O'Leary, 2009), perseverance and persistence (Fleet, Kitson, Cassady, & Hughes, 2007;Sinclair, 2008), optimism (Chong & Low, 2009;Le Cornu, 2009), sense of humour (Bobek, 2002;Jarzabkowski, 2002), emotional intelligence (Chan, Lau, Nie, Lim, & Hogan, 2008), willingness to take risks (Sumsion, 2003) and flexibility (Le Cornu, 2009). Such attributes may assist early career teachers to 'bounce back' despite the challenges of the first years of teaching.…”
mentioning
confidence: 99%
“…Considering gender, some studies have indicated that females' level of commitment is higher than males' levels of commitment (Coladarci, as cited in Chan et al, 2008;Park, 2005). But, the findings of Borman and Dowling (2008) indicated lower commitment of females.…”
Section: Professional Commitmentmentioning
confidence: 99%